Uterine sex cord tumour- Management dilemma - Mohamad Nasir S,; Lim PS,; Swaminathan M,; Hatta MD,; Mohd Hashim O, (Department of Surgery, UKM Medical Centre, 2011)
Uterine sex cord tumour is a very rare tumour with uncertain management strategies and prognosis. A 61-year-old, nulliparous, who was not on hormone replacement therapy, presented with first episode of postmenopausal bleeding. A transvaginal scan revealed an enlarged uterus with thick endometrial lining and features of multiple degenerated fibroid. Endometrial biopsy was negative for malignancy. Computed tomography of the abdomen and pelvis confirmed the mass, with atrophic ovaries and incidental finding of bilateral hydronephrosis requiring stentings. Otherwise, there were no pelvic lymph nodes enlargement. Our impression was a uterine sarcoma and we decided for total abdominal hysterectomy with bilateral salpingooophorectomy. Surprisingly, the histology report confirmed uterine sex cord tumour. There are less cases of recurrence and there is no general consensus on the management. However, we decided for adjuvant chemotherapy (BEP regime) as the malignant cells infiltrated more than half of myometrial thickness, with good outcome.